Increased incidence of distal humeral fractures and surgical treatment in 0- to 18-year-old patients treated in Finland from 1987 to 2010. (December 2013) - Salonen, A.; Pajulo, O.; Lahdes-Vasama, T.; Välipakka, J.; Mattila, V. M.
Background: Studies of pediatric and adolescent fractures in general report a significant increase in the incidence of upper-extremity fractures as well as in their surgical treatment. The aim of this study was to determine the trends of the incidence and treatment of distal humeral fractures in hospitalized 0- to 18-year-old patients in Finland. Method: The study included the entire pediatric and adolescent (<19 years) population in Finland during the 24-year period from 1 January 1987 to 31 December 2010. Data on hospitalized patients were obtained from the nationwide National Hospital Discharge Registry where information is collected from all hospital categories (private, public, and other). Surgical treatment was categorized into three groups; (1) reposition with casting; (2) reposition or reduction and osteosynthesis; (3) reposition or reduction and external-fixation and other fixation methods. Patients were classified into three groups according to age: 0–6 years, 7–13 years, and 14–18 years. Annual incidences were calculated using the annual mid-year population census obtained from the Official Statistics of Finland. Results: During the 24-year study period, there were a total of 12, 590 hospitalizations with a main or secondary diagnosis of distal humeral fracture. In children aged 0–12 years the overall incidence of hospitalization increased 30 % during the 24-year study period, from 4.5 per 10, 000 person-years in 1987 to 5.8 per 10, 000 person-years in 2010. There were a total of 5, 548 operations. During the study period, surgical treatment by repositioning or reduction with osteosynthesis due to a distal humeral fracture increased by fivefold in patients aged <6 years and by twofold in patients aged 7–12 years of age. The incidences of fracture and treatment in children older than 13 years did not change. Conclusion: The incidence of distal humeral fractures and the incidence of repositioning with osteosynthesis increased remarkably in prepubertal children during the 24-year study period in Finland.